PENGEMBANGAN MEDIA DIGITAL INTERAKTIF PADA MATERI PENYAJIAN DATA TUNGGAL KELAS V SDN 4 KASUGENGAN LOR - Arief Hidayat Afendi; Teti Sugesti (PGSD Universitas Muhammadiyah Cirebon, 2022)
Student in understanding the material, and the difficulty of the teacher to explain the material in the learning process is caused by the use of limited learning media or learning materials, besides the use of digital learning media which results in the mathematics learning process carried out by the teacher being less than optimal. This study aims to develop a digital interactive media based on E-Book in Mathematics V, by using the research and development (R&D) method of the Borg and Gall model which was modified by Sugiyono in order to overcome problems and become an alternative for teacher and student in the Mathematics learning process in elementary School and to determine the product that has been developed through the material validation and media validation stages. The Borg and Gall model that has been modified by Sugiyono used consists of five development steps, namely potential and problems, information gathering, product design, design validation, and design revision. The data collection instrument used was a likert scale questionnare with quantitative descriptive data analysis and percentages.the results of this study indicate that interactive digital media based on E-Book on single data presentation materials are very feasible to use according to media experts and material experts because they are in accordance with feasibillity indicators. Keywords: Intructional Media, Interaktif Digital E-Book, Mathematics.